2017
DOI: 10.5465/amj.2014.0487
|View full text |Cite
|
Sign up to set email alerts
|

“Devils May Sit Here:” The Role of Enchantment in Institutional Maintenance

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 88 publications
3
92
1
Order By: Relevance
“…Nazi concentration camps have been viewed as settings where institutional work creating social oppression was undertaken (Marti and Fernandez, 2013). Institutional work maintaining professional occupations goes on in museums, law courts, restaurants, and hospitals through the everyday actions of curators (Blagoev, Felten, and Kahn, 2018), lawyers and advocates (McPherson and Sauder, 2013;Siebert, Wilson, and Hamilton, 2017), chefs (Gill and Burrow, 2018), and physicians and nurses (Reay, Golden-Biddle, and GermAnn, 2006;Kellogg, 2009;Wright, Zammuto, and Liesch, 2017). Place was not the focus in the aforementioned studies, but Lawrence and Dover (2015) have drawn attention to how place influences institutional work, showing how places serve as ''social enclosures'' that contain, ''signifiers'' that mediate, and ''practical objects'' that complicate institutional work.…”
Section: Maintaining Places Of Social Inclusionmentioning
confidence: 99%
“…Nazi concentration camps have been viewed as settings where institutional work creating social oppression was undertaken (Marti and Fernandez, 2013). Institutional work maintaining professional occupations goes on in museums, law courts, restaurants, and hospitals through the everyday actions of curators (Blagoev, Felten, and Kahn, 2018), lawyers and advocates (McPherson and Sauder, 2013;Siebert, Wilson, and Hamilton, 2017), chefs (Gill and Burrow, 2018), and physicians and nurses (Reay, Golden-Biddle, and GermAnn, 2006;Kellogg, 2009;Wright, Zammuto, and Liesch, 2017). Place was not the focus in the aforementioned studies, but Lawrence and Dover (2015) have drawn attention to how place influences institutional work, showing how places serve as ''social enclosures'' that contain, ''signifiers'' that mediate, and ''practical objects'' that complicate institutional work.…”
Section: Maintaining Places Of Social Inclusionmentioning
confidence: 99%
“…Empirical evidence about the potential positive and negative effects of co-creation, in terms of individual, organizational and societal value, should give us a more nuanced understanding of the co-paradigm and its practical implications for public administration. We contend that this lack of systematic knowledge represents a stage in our enchantment (Jenkins 2000;Siebert, Wilson, and Hamilton 2017) with the co-paradigm, and at the same time an impetus for disenchantment (Weber 2005).…”
Section: Co-productionmentioning
confidence: 99%
“…The normative assumption behind the magic nature of co-creation is that the outcome of (public) services co-created by users and professionals ought to be 'better services'. But are they, necessarily, or have we been 'enchanted' (Siebert, Wilson, and Hamilton 2017) by their intuitive appeal? In this editorial, we call for constructive disenchantment with the magic that surrounds co-design, co-production and value co-creation in public services.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have also shown how the Scottish Legal System reproduced the status quo from emplacement, enchantment, and enacting space (Siebert et al, 2017), and demonstrated how the three types of spaces played a historical role in transforming an all-women's college into a co-ed institution (Liu and Grey, 2018) and in negotiating gendered representations of space (Tyler and Cohen, 2010). Even though these studies embrace Lefebvre's (1991) triad, researchers typically focus on macro organizational levels.…”
Section: Developing a Tension-based Approach To The Study Of Workpacesmentioning
confidence: 99%